The Role of the Government on Precarious Work among Fishermen in Semporna, Sabah - Asniah Asgali; Fazli Abd Hamid (Penerbit Universiti Malaysia Sabah, 2018)
Precarious work is a job that is uncertain, unpredictable and has risky work practices. Employers have the potential to manipulate the conditions of employment that they need to support their employees through the forms of precarious employment relationships such as no service contracts and low wages. These characteristics of precarious work contradicts the standard employment relationship systems, which should be accepted by an employee based on the Employment Act 1955 and the Sabah Labor Ordinance. This study is using a qualitative by interviewing the employers and employees as well as using questionaire to support the data. This paper attempts to analyze the role of the government in controlling the formation of precarious work characteristics among fishermen in Sabah especially in the research location in Semporna. The findings indicate that the lack of supervision of workers against employment laws in the fisheries sector are being ignored and misused in many of the work regulations.